1999
DOI: 10.1117/12.365877
|View full text |Cite
|
Sign up to set email alerts
|

<title>Improving video processing performance using temporal reasoning</title>

Abstract: In this paper, we present a system, called MediABS, for extracting key frames in a video segment. First we will describe the overall architecture of the system and we will show how our system can handle multiple video formats with a single videoprocessing module. Then we will present a new algorithm, based on color histograms. The algorithm exploits the temporal characteristic of the visual information and provides techniques for avoiding false cuts and eliminating the possibility of missing true cuts. A discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Methods using spatial and temporal skips and histogram analysis [2,3,4,5] recognize that, spatially or temporally, many video frames are very similar and that is redundant to analyze them all. These approaches confirmed that the use of color histograms better accommodates the flow motion of the objects and the camera within the same shot.…”
Section: Related Workmentioning
confidence: 99%
“…Methods using spatial and temporal skips and histogram analysis [2,3,4,5] recognize that, spatially or temporally, many video frames are very similar and that is redundant to analyze them all. These approaches confirmed that the use of color histograms better accommodates the flow motion of the objects and the camera within the same shot.…”
Section: Related Workmentioning
confidence: 99%